Evaluation report on Mahila Samriddhi Yojana - Planning Commission (Planning Commission, 1996)
The Mahila Samriddhi Yojana (MSY), launched in 1993 by the Department of Women and Child Development, aims to empower rural women through financial inclusion, self-reliance, and promotion of thrift habits. The evaluation conducted by the Programme Evaluation Organisation (PEO) assessed its implementation across 28 districts in 16 states, highlighting performance, impact, and operational challenges. Key findings indicate substantial inter-state variations, low average deposits, high account closure rates, and procedural complexities that limited scheme effectiveness. Success was linked to active involvement of local organizations, while underperformance stemmed from inadequate awareness, complex rules, and high operational costs. Recommendations include simplifying procedures, enhancing training and awareness, incentivizing local participation, and establishing robust monitoring mechanisms. The report concludes that while MSY has laid a foundation for women’s empowerment, targeted improvements are necessary to achieve sustainability and greater participation.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission
Keywords: Mahila Samriddhi Yojana; Rural Women Empowerment; Financial Inclusion; Savings Scheme; Programme Evaluation Organisation; Operational Challenges; Account Closure; Training and Awareness; Local Organization Participation; Operational Cost Management